Peningkatan kapasitas reproduksi domba serta manajemen induk bunting dan perawatan cempe pada peternak milenial KUBE Barokah di Desa Kondangjajar Kabupaten Pangandaran - Wulansari, Asri; Khoerunnisa, Nurani; Fitri, Siti Ulfah Rifa'atul (Farmers : Journal of Community Services, 2026)
This community-service program in Kondangjajar Village (Pangandaran) strengthened millennial farmers’ capacity in sheep reproduction to improve herd productivity and support stunting reduction. Using a participatory, practice-oriented approach, we engaged the KUBE Barokah farmers group in Kondangjajar Village (11 members; 70 sheep), conducted a pre- and post- assessment, prepared a concise flyer, and introduced reproduction calendars to standardize record-keeping (estrus, mating, expected lambing, weaning). Barn-based instruction covered estrus detection and timing of mating (natural service and the ram effect), recommended male:female ratios in colony systems, nutrition of pregnant and dry ewes (with emphasis on calcium near parturition and gradual diet transitions), and neonatal care (colostrum within ≤2 h, navel hygiene, warming, identification, weighing). Follow-up monitoring documented improved knowledge, consistent calendar use, and early adoption of key behaviors, including timely colostrum provision, application of a 1.5–2-month dry period, and more accurate mating within the 24–48 h estrus window. The intervention proved feasible and acceptable for resource-limited smallholders, creating a foundation for measurable gains in conception/lambing rates, reduced neonatal loss, better weaning weights, and stronger household access to animal-source foods. Continued mentoring and systematic recording are planned to quantify technical–economic outcomes and to scale practices through peer champions.